When moments matter: Finding answers with rapid exome sequencing. Issue 2 (24th December 2019) - Powis, Zöe; Farwell Hagman, Kelly D.; Blanco, Kirsten; Au, Margaret; Graham, John M.; Singh, Kathryn; Gallant, Natalie; Randolph, Linda M.; Towne, Meghan; Hunter, Jesse; Shinde, Deepali N.; Palmaer, Erika; et al.
Abstract: Background: When time is of the essence in critical care cases, a fast molecular diagnosis is often necessary to help health care providers quickly determine best next steps for treatments, prognosis, and counseling of their patients. In this paper, we present the diagnostic rates and improved quality of life for patients undergoing clinical rapid exome sequencing. Methods: The clinical histories and results of 41 patients undergoing rapid exome sequencing were retrospectively reviewed. Results: Clinical rapid exome sequencing identified a definitive diagnosis in 13/41 (31.7%) and other relevant findings in 17 of the patients (41.5%). The average time to verbal report was 7 days; to written report was 11 days. Conclusions: Our observations demonstrate the utility and effectiveness of rapid family‐based diagnostic exome sequencing in improving patients care. Abstract : The ability of a health care provider to order testing and counsel families within 7 days is advantageous for patients. About 31.7% received a diagnosis and 92.7% of providers reported ordering testing to aid in prognosis and medical management decisions, including potential end of life decisions.